Edaphic conditions of different islands under different hydrological regimes in the coastal zone of Bangladesh - Ahmed, Ashfaque; Ohlson, Mikael; Hoque, Sirajul; Moula, Md Golam (Dhaka University Journal of Biological Sciences, 2011)
Physical and chemical properties of soils from the southern coastal zone of Bangladesh were studied to understand the effect of inundation on different soil variables. Soil samples were collected from three different islands representing different hydrological regimes, viz. Char Motherbunia (Island I) is inundated twice daily, Char Taposhi (Island II) is inundated by high tide and Char Kashem (Island III) is totally raised, inundated only during storm surges. Three transects in each island perpendicular to the river Buragauranga were established. Five soil samples, each with a composite of five sub-samples, were collected from each transect, 15 variables were tested from total 15 samples of each island. To test the variations among the islands and within the island, ANOVA was used. Soils of the three islands were found to be rather similar in chemical properties, although there were some significant differences in pH and potassium concentration. The results indicated that broad-scale hydrology did not effect the variation found in the edaphic condition rather duration and amplitude may be responsible for some observed variation. A correlation matrix of the soil variables showed a strong correlation among chemical elements and that the majority of elements were significantly correlated with pH. Key words: Edaphic conditions; Coastal zone; Hydrological regimes; Tidal amplitude DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8941 DUJBS 2010; 19(1): 27-40